2012
DOI: 10.5539/ibr.v5n11p1
|View full text |Cite
|
Sign up to set email alerts
|

Pecking-Order or Static Trade-off Theory in Family Firms? Evidence from Belgium

Abstract: The purpose of this paper is to investigate whether a difference can be stated in the family firms' financial choices. Using the Shyam-Sunder and Myers model, our research focus on the financial behaviour of family and non-family privately held firms in Belgium. Out of a sample of 210 privately held firms for the period 2002-2010, panel data methodology is employed to estimate Pecking-Order and Static Trade-off models. Our results show that although neither Pecking Order nor Static Trade-off Theory seems to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
6
1
2
Order By: Relevance
“…A method which is frequently used for testing the POT is based on the analysis of a firm's net debt issued to finance the "funds flow deficit", given by adding dividend payments, capital expenditure, the net increase in working capital, the current portion of long-term debt and by subtracting the operating cash flows after interest and taxes (Shyam-Sunder & Myers, 1999). In addition to this method used by several studies (e.g., Chirinko & Singha, 2000;Frank & Goyal, 2003;Bauweraerts & Colot, 2012), the POT has been tested on the basis of the relationship between profitability and firm's leverage (e.g., Titman & Wessels, 1988;Baskin, 1989;Allen, 1993). The negative correlation between profitability and leverage is a factor that validates the theory since only profitable firms have the opportunity to finance new investments with retained earnings rather than through a new debt and/or equity issuance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A method which is frequently used for testing the POT is based on the analysis of a firm's net debt issued to finance the "funds flow deficit", given by adding dividend payments, capital expenditure, the net increase in working capital, the current portion of long-term debt and by subtracting the operating cash flows after interest and taxes (Shyam-Sunder & Myers, 1999). In addition to this method used by several studies (e.g., Chirinko & Singha, 2000;Frank & Goyal, 2003;Bauweraerts & Colot, 2012), the POT has been tested on the basis of the relationship between profitability and firm's leverage (e.g., Titman & Wessels, 1988;Baskin, 1989;Allen, 1993). The negative correlation between profitability and leverage is a factor that validates the theory since only profitable firms have the opportunity to finance new investments with retained earnings rather than through a new debt and/or equity issuance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing research suggests that family firms would target their debt level to maintain the family control of the business. Moreover, other existing empirical research highlights that family firms seem to pursue indebtedness target ratio (Bauweraerts & Colot, 2012) and can approach their debt target ratio more quickly than non-family firms (Lopez-Gracia & Sanchez-Andujar,2007). …”
Section: Theoretical Framework For Family Firms' Capital Structurementioning
confidence: 99%
“…Without going into a detailed analysis of the research literature, it is nevertheless worth noting the funds flow deficit computed by adding dividend payments, capital expenditures, net increase in working capital, current portion of long-term debt and subtracting the operating cash flows, after interest and taxes (Shyam-Sunder & Myers, 1999;Chirinko & Singha, 2000;Bauweraerts & Colot, 2012) and the numerous indices that are used to measure a firm's level of debt or its degree of profitability (Fama & French, 2002;Frank & Goyal, 2003;Leary & Roberts, 2005;Panno, 2003;Lemmon & Zender, 2006;Bharath, Pasquariello, & Wu, 2009;Mazen, 2012). From the analysis of these indicators the studies have tried to delineate the order of preference followed by firms for their financing.…”
Section: Methodsmentioning
confidence: 99%
“…Al Manaseer et al (2011) provided evidence for the POT against target capital structure theory in the UK market. Bauweraerts and Colot (2012) revealed that neither POT nor Static Trade-off Theory can explain why family rather than non-family firms are more likely to adopt an indebtedness target ratio. In his examination of a sample of French companies, Mazen (2012) confirmed the explanatory power of the POT.…”
Section: Literature Reviewmentioning
confidence: 99%